An unusual cause of ascites and pleural effusion in an elderly woman: Sarcoidosis presenting with parailiac lymph node involvement - Şahin, Abdurrahman; Artaş, Hakan; Artaş, Gökhan (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Şahin A, Artaş H, Artaş G. An unusual cause of ascites and pleural effusion in an elderly woman: Sarcoidosis presenting with parailiac lymph node involvement. Turk J Gastroenterol 2020; 31(10): 731-3.